Finger on the Trigger of Destiny: A Study of Their Eyes Were Watching God - Nazki, Sameeul Haq (International Journal of Sustainability in Research, 2024)
This study explores the metaphorical idea of “a finger on the trigger of destiny, which finds expression in Zora Neale Hurston’s 1937 book Their Eyes Were Watching God. In the context of interpersonal interactions and cultural expectations, the story follows Janie Crawford on her path to self-discovery and empowerment. This research describes how Janie navigates and ultimately creates her destiny through an examination of her three marriages, her search for self-identity, and the symbolic motifs of the horizon and the pear tree. The Eatonville community’s impact on path is also examined in the study. Janie is a strong example of self-determination who embraces her goals and takes charge of her life, embodying the novels larger themes of autonomy, gender, and race. This examination highlights how Hurston’s depiction of the human fight for identity and agency remains timeless. This study aims to dissect how Janie navigates her destiny amidst the pressures and constraints imposed by society, her relationships, and her inner aspirations. In this study, aim is to delve into the profound themes embedded within Hurston’s work, with a particular focus on the role of fate and agency in shaping Janie’s journey. Through a meticulous analysis of character dynamics, narrative structure, and socio-cultural context, we aim to unravel the intricate tapestry of Their Eyes Were Watching God and illuminate its enduring relevance in contemporary discourse.